Efektivitas permainan story card terhadap kemampuan mengingat kosakata bahasa inggris siswa sekolah dasar - Ramadhani, Amalia; Lestari, Magfira Diah (Fakultas Sastra, 2023)
Abstrak: Learning to use story card media can help children to memorize and quickly remember the words they have learned. This study aims to determine the effect of story card games on the ability to remember the English vocabulary of SDIT Plus Qurthuba students. The study uses a pre-posttest design experimental method. The participants in this study were 22 students in class III C which were divided into two groups, the experimental group and the control group. This study uses independent sample t-test data analysis techniques using JASP 0.14.1.0 software. The results showed that there was an influence of story card games on the ability to remember the English vocabulary of SDIT Plus Qurthuba students Kata Kunci: English vocabulary, story cards game, elementary student